2018
DOI: 10.2166/wpt.2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Improving flood monitoring in rural areas using remote sensing

Abstract: Precise information on the extent of inundated land is required for flood monitoring, relief, and protective measures. In this paper, two spectral indices, Normalized Difference Water Index (NDWI) and Modified Normalized Difference Water Index (MNDWI), were used to identify inundated areas during heavy rainfall events in the Tarwin catchment, Victoria, Australia, using Landsat-8 OLI imagery. By integrating the assessed condition of levees, this research also explains the inefficiency of the flood control measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Khosravani et al (2017) have shown that the NDWI index is more accurate than the other indices for change detection of lake Parishan. Ghofrani et al, 2019…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khosravani et al (2017) have shown that the NDWI index is more accurate than the other indices for change detection of lake Parishan. Ghofrani et al, 2019…”
Section: Resultsmentioning
confidence: 99%
“…Flooding is one of the most common and destructive natural hazards affecting human life and creating many economic problems around the world. Therefore, accurate monitoring of flood events is increasingly necessary to gain insight about both causes and remedies (Refice et al, 2017;Ghofrani et al, 2019). The first concern in flood management plans is mapping flood area.…”
Section: Introductionmentioning
confidence: 99%
“…In Shouguang, both algorithms based on Sentinel-1 and Sentinel-2 with random forest classification for rivers showed OA values of 85.22% and 95.45%, respectively (Huang and Jin 2020). Furthermore, for rural watershed areas in Australia, using two algorithms based on Landsat Oli 8 imagery with unsupervised classification proved to be effective, with OA values of 96.04% and 95.70%, respectively (Ghofrani et al 2019). Implementation on rivers and lakes in Canada, the Tennessee River in the US, the Swedish lake Lungsjön, and Mongolia's Lake Khar-Us using Sentinel-2 imagery showed outstanding accuracy with consecutive OA values based on the NDWI (0.97, 0.965, 0.94, and 0.925) and the MNDWI (0.97, 0.962, 0.96, and 0.945;Niu et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Blöschl et al (2017) larger part of Bosnia and Herzegovina faced altered temporal flood patterns which resulted in earlier floods. Monitoring flood events is critical for gaining insights into causes and flood damages (Ghofrani et al, 2019;Refice et al, 2018).…”
Section: Introductionmentioning
confidence: 99%